A bio-economic model of integrated crop-livestock farming systems: The case of the Ginchi watershed - Okumu, B.N.; Jabbar, M.A.; Colman, D.; Russell, N. (CAB International, 2002)
This chapter uses one particular bio-economic model, first, to explore some questions and hence generate information pertaining to the complex interactions existing in an integrated crop-livestock farming system in Ethiopia. Secondly, it examines various ways in which such a model may be used to assess, exante, the likely impact of multiple technology adoption on such systems under a set of policy scenarios. The chapter is organized as fallows. The next section describes the Ginchi-watersted integrated crop-livestock production system and highlights a watershed community as opposed to a purely household level of analysis. The third section explains some features of the Ginchi-watershed bio-economic model, while the fourth section discusses model results and policy implications. The final section outlines the main policy conclusions.